2020
DOI: 10.3390/en13123202
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Coordination Strategies for Load Service Entity and Community Energy Systems Based on Centralized and Decentralized Approaches

Abstract: The energy interaction among a load service entity and community energy systems in neighboring communities leads to a complex energy generation, storage, and transaction problem. A load service entity is formed by a local electricity generation system, storage system, and renewable energy resources, which can provide ancillary services to customers and the utility grid. This paper proposes two coordination schemes for the interaction of community-based energy systems and load service entities based on game-the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…While various operational scenarios were studied, only few players (nine community groups only) were considered in the coalition formation. Similarly, Longxi Li [75] have proposed a cost-sharing scheme developed according to the Shapley value method. However, only four players are considered, thereby raising the issue of computational tractability and hence the practical application of the proposed redistribution mechanism is limited.…”
Section: B Sharing Of Energy Cost and Financial Gain In Energy Communitiesmentioning
confidence: 99%
“…While various operational scenarios were studied, only few players (nine community groups only) were considered in the coalition formation. Similarly, Longxi Li [75] have proposed a cost-sharing scheme developed according to the Shapley value method. However, only four players are considered, thereby raising the issue of computational tractability and hence the practical application of the proposed redistribution mechanism is limited.…”
Section: B Sharing Of Energy Cost and Financial Gain In Energy Communitiesmentioning
confidence: 99%
“…A major challenge in DR is the coordination of the loads in distribution grids with different voltage levels. In particular, the coordination of various-size loads may hurdles achieving the expected frequency response rates of the system and reaching reserve capacity reduction goals [49], [50]. Aggregators contract with energy customers to inclining their flexible consumption or production; aggregators then amalgamate energy consumers' flexibility and renovate it for market services, e.g., for Balance Responsible Parties (BRP) [51].…”
Section: Demand Sidementioning
confidence: 99%
“…The work revealed that, depending on the configuration in the consumer and prosumer communities, the economic gains could increase. Another case of CEMs was addressed in [30] by proposing two schemes based on the coordination of generation sources and energy storage within a community. These schemes considered game theory, Karush-Kuhn-Tucker conditions, and strong duality theorem to allow achieving a win-win situation for all participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The state of charge of the SB for the rest of the periods t is obtained by (29). Constraint (30) guarantees that at the end of the day t = |T| the SoC sb u,t of the SB is equal to its storage capacity, C sb u , while (31) guarantees that the SoC of SB throughout the day does not exceed the C sb u capacity.…”
Section: Energy Storage Constraintsmentioning
confidence: 99%